Multicultural approach in learning beginning writing in elementary school - Mahendra, Yasinta; Suprapto, Irawan (Journal of Research in Social Science and Humanities, 2023)
Multicultural approach in learning beginning writing is basically a need for teachers and students in the learning process, because multicultural education can be used as an alternative to success in learning. The purpose of this study is to see how the effectiveness of the role of culture, in this case multicultural, is used by teachers as a means as one of the ways to improve the ability to write beginnings in grade 2 (two) elementary schools in several schools located in the district of Kotabumi Selatan, North Lampung Regency. This type of research is experimental research using a 2x2 factorial design. Data in this study were collected using learning achievement tests and learning motivation questionnaires, and analysed using two-way ANOVA and sheffe test. The results in the study showed that; 1) there was a gap in learning achievement between experimental group students and control group students; 2) there was a difference in learning achievement between students who had high motivation in both groups; 3) there was a difference in learning achievement between students who had low motivation in both groups; 4) multicultural approach was proven to improve students' beginning reading ability.